(untitled) (Impact: Journal of Transformation, 2024)
The study sought to examine the influence of corporate governance dimensions on SACCOs’ financial performance in Nairobi County. Specifically, the study sought to determine the effect of board independence, board accountability, audit committee and financial disclosure on financial performance of SACCOS in Nairobi County. The study was anchored on agency, stewardship, and stakeholder theories. This research used descriptive survey design. The target population was the heads of finance and administration in all the 43 SACCOs in Nairobi County. The study applied census given that the target population was small. Secondary data on return on assets, total deposits, total assets and non-performing loans was collected from the annual reports of the SACCOs. Primary data was collected using semistructured questionnaires. Quantitative data was then analyzed using inferential and descriptive statistics which comprised of mean, frequencies, standard deviation, and percentages. The study found that board independence, board accountability and audit committee have a positive and significant effect on the financial performance of SACCOs in Nairobi County, while financial disclosure has a positive and insignificant effect on the financial performance of SACCOs in Nairobi County. The study recommends that SACCOs should select independent members of the boards to help the societies run honestly and efficiently since they are not under the influence of the management teams. In addition, SACCOs should make sure that the board of directors actively oversees and holds management accountable for financial decisions, risk management, and strategic planning. They should select the audit committee to monitor financial reporting, audit process, internal control system of the organization, and legal and regulatory conformity. They should also clearly define the roles and responsibilities of the audit committee in the SACCO’s bylaws. Further, SACCOs should also establish a system for regular reporting to the board on financial performance, risk exposure, and compliance with financial policies and regulations.